A produção do espaço e da habilitação: o programa minha casa minha vida em Russas - Ceará - Sousa, Jéssica Liana de (2018)
This study aims to analyze the repercussions of the “Minha Casa Minha Vida” program (PMCMV – My House My Life) in the production of space of the city of Russas, located in the Microregion of BaixoJaguaribe, Ceará, Brazil. It seeks, therefore, to identify the space producing agentsand to verify how the expansion of the city has been directed from the perspective of the mentioned program. The proposed subject is important to understand the processes and socio-spatial transformations caused by the implementation of a federal policy - the PMCMV - in a city considered to be "small". The PMCMV is a federal program created in 2009 for housing finance, divided into three groups: Level 1, Level 2 and Level 3 Banners are defined based on family incomes. Track 1: with monthly income of up to R$ 1.8 thousand; Range 2: limit monthly income up to R$ 4 thousand; Range 3: Monthly income limit up to R$ 9 thousand. In 2016, an intermediate band was created, Range 1.5 for families with income up to R$ 2,600. In 2016, an intermediate level was created, Level 1.5, for families with incomes of up to R$ 2.350. Preliminary results showed that in Russas by the end of 2017 all the developments built were destined to levels 2 and 3. The research has as main objective the production and expansion of the real estate sector in the urban space of the city. It is understood that space is a fundamental condition for the reproduction of society, therefore a historical product and social content. In this perspective, the housing policy is analyzed considering the relation between State and capital real estate, the housing projects’ forms of promotion, as well as the urban characteristics of these projects. It discusses the effects of housing projects financed by the State and its scales of operation, especially on the scale of the city. The research is based on the readings about (re) production of the urban space, space producing agents and studies related to the housing production. Based on the theoreticalmethodological reference, data and information were collected in the public administration sectors of the city of Russas (Secretary for Infrastructure and Secretary for Development) and institutions and bodies such as the JoãoPinheiro Foundation, Brazilian Institute of Geography and Statistics (IBGE), the State Research Institute of Ceará (IPECE). In addition, fieldwork was carried out using some methodological procedures: landscape observation, photographic records, semi-structured interviews with employees of the institutions and real estate developers, and questionnaires to obtain direct information from the residents in the projects visited. For direct research with the residents, two projects were selected: Santiago Residential I (Level 3) and the first project implemented in the city in 2009 (Level 2). The study found that the provision of housing of social interest aimed at the low-income population is allocated in areas with little infrastructure and services; that there was a marked increase in the creation of subdivisions and real estate projects aimed to the higher income groups - Levels 2 and 3 - and that in fact the program boosted the real estate market, as well as the reproduction of socio-spatial inequalities, particularly in the city of Russas-CE.